A YFe 4 B 4 Alloy magnetic wave absorbing material and its preparation process

By preparing the magnetic wave absorbing material of YFe4B4 alloy, using the optimized process flow and atomic ratio, the problem of unsatisfactory absorption performance of Fe-based alloy in the 2-8GHz frequency band is solved, and excellent absorption effect and economy in this range are achieved Improved efficiency.

CN114824826BActive Publication Date: 2024-12-20ANHUI JIHUA NEW MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210306988.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-25
Publication Date
2024-12-20
Estimated Expiration
2042-03-25

AI Technical Summary

Technical Problem

The existing Fe-based alloy absorbing materials have poor absorption performance in the 2-8GHz frequency band, especially in the S-band, and are difficult to meet the excellent absorption requirements in the 2-8GHz range.

Method used

The magnetic wave absorbing material of YFe4B4 alloy is prepared by batching, smelting, ball milling, molding, sintering and grinding. The atomic ratio is optimized to YFe4-x-yMnxSnyB4-zSiz. Combined with vacuum smelting, ball milling and microwave sintering technology, it is prepared with An alloy magnetic wave absorbing material with excellent wave absorbing performance.

Benefits of technology

The absorption bandwidth and wave absorption performance are significantly improved in the 2-8GHz frequency band, reducing production costs, suitable for large-scale production, and improving market economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114824826B_ABST
    Figure CN114824826B_ABST
Patent Text Reader

Abstract

The present invention provides a YFe4B4 alloy magnetic wave absorbing material and a preparation process thereof, and relates to the technical field of wave absorbing materials. The alloy magnetic wave absorbing material is YFe 4‑x‑ y Mn x Sn y B 4‑z Si z , wherein 0.1≤x≤0.8, 0.2≤y≤0.6, 0.1≤z≤0.8, and the preparation method of the alloy magnetic absorbing material mainly includes the steps of batching, smelting, ball milling, molding, sintering, grinding and the like. The present invention overcomes the shortcomings of the prior art, and the prepared gold magnetic absorbing material has the advantages of wide absorption bandwidth and excellent absorbing performance within 2‑8 GHz. The preparation process of the material is easy to master and the production cost is low, so it is suitable for large-scale production and use, thereby improving the economic benefits of the market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wave absorbing materials, and in particular to a YFe4B4 alloy magnetic wave absorbing material and a preparation process thereof. Background Art

[0002] In recent years, with the widespread application of various electronic products, microwave radiation has become a new source of pollution, posing a serious threat to human health. For this reason, people have developed various absorbing materials to protect against microwave radiation. At the same time, the development of stealth technology in the military has promoted the development of absorbing materials.

[0003] Traditional absorbing materials mainly include ferrite and magnetic metal (alloy) powders. Although ferrite is the most widely used and effective anti-electromagnetic interference material, its application is greatly limited due to its low saturation magnetization, poor thermal stability and corrosion resistance. Magnetic metal powders have high Curie temperature, good thermal stability, good saturation magnetization and particle shape effect, high complex magnetic permeability and low eddy current loss, and small matching thickness (millimeter level), so they have good application prospects as electromagnetic wave absorbers.

[0004] At present, the most widely used soft magnetic alloy powders are mainly Fe, Co, Ni and their alloy powders. Since Fe resources are relatively abundant and its price is relatively low compared to Co and Ni, and the absorbing performance of Fe-based alloy absorbing materials is also good, they are widely used, mostly in the 2-18GHz frequency band. However, the absorbing performance of the Fe-based alloy absorbing materials currently developed in the S (2-4GHz) and C (4-8GHz) bands, especially in the S band, is still not ideal. Therefore, it is of great significance to develop an absorbing material with good absorbing performance in the 2-8GHz range. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a YFe4B4 alloy magnetic absorbing material and a preparation process thereof, so that the prepared gold magnetic absorbing material has the advantages of wide absorption bandwidth and excellent absorbing performance within 2-8GHz. The preparation process of the material is easy to master and the production cost is low, so it is suitable for large-scale production and use, thereby improving the economic benefits of the market.

[0006] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:

[0007] A YFe4B4 alloy magnetic wave absorbing material, wherein the alloy magnetic wave absorbing material has the following atomic ratios: YFe 4-x-y Mn x Sn y B 4-z Si z ;

[0008] The preparation method of the alloy magnetic wave absorbing material comprises the steps of batching, smelting, ball milling, molding, sintering, grinding and the like.

[0009] Preferably, the ingredients are: metal Y, Fe, Mn, Sn, Si, B are selected as raw materials, according to YFe 4-x-y Mn x Sn y B 4-z S iz (0.1≤x≤0.8; 0.2≤y≤0.6; 0.1≤z≤0.8), mix the ingredients in the atomic ratio to obtain a raw material mixture.

[0010] Preferably, the smelting is: placing the raw material mixture in a vacuum melting furnace for smelting under argon protection, and casting to obtain an alloy ingot.

[0011] Preferably, the ball milling comprises: crushing the alloy ingot into coarse powder with a particle size of less than 0.5 mm, and then sieving it under a 50-mesh sieve to obtain the alloy coarse powder; placing the crushed alloy coarse powder and zirconia balls in a zirconia tank at a mass ratio of 18:1, and ball milling for 10-24 hours under the protection of anhydrous ethanol at a ball mill speed of 200-350r / min to obtain ball-milled powder.

[0012] Preferably, the forming is as follows: the ball milled powder is taken out from a nitrogen-protected glove box, dried, and then pressed into a blank with a diameter of 20 mm and a height of 10 mm.

[0013] Preferably, the sintering is: placing the blank into a vacuum microwave sintering furnace for high-temperature sintering, the sintering temperature is 1000-1060° C., the temperature is kept for 20-40 minutes, and the microwave frequency is 2.0-3.2 kW to obtain a sintered blank;

[0014] Preferably, the grinding is as follows: the sintered blank is crushed, ground into fine powder using an agate mortar, and then sieved through a 200-mesh sieve to obtain the alloy absorbing powder. The sintered blank is taken out and crushed, and then ground and sieved to obtain the alloy absorbing powder.

[0015] The present invention provides a YFe4B4 alloy magnetic wave absorbing material and a preparation process thereof, which has the following advantages over the prior art:

[0016] (1) The alloy magnetic absorbing material prepared in this application can have excellent microwave absorption effect and bandwidth in the 2-8 GHz frequency band, effectively ensuring the performance of the material and improving the application range of the material;

[0017] (2) The material in the present application can be obtained through batching, smelting, ball milling, molding, sintering and grinding. The process is relatively simple and easy to operate, which is suitable for large-scale production and effectively reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a process flow chart of the preparation method of the present invention;

[0019] Figure 2 This is a test result diagram of the alloy absorbing material of Example 1;

[0020] Figure 3 This is a graph showing the test results of the alloy absorbing material of Example 2;

[0021] Figure 4 This is a graph showing the test results of the alloy absorbing material of Example 3. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Embodiment 1:

[0024] A YFe4B4 alloy magnetic absorbing material:

[0025] (1) Using metal Y, Fe, Mn, Sn, Si, and B with a purity of ≥99.9% as raw materials, according to YFe 3.2 Mn 0.5 Sn 0.3 B 3.8 Si 0.2 Atomic proportioning for batching;

[0026] (2) melting in a standard vacuum melting furnace under argon protection and casting to obtain an alloy ingot;

[0027] (3) crushing the obtained alloy ingot into coarse powder with a particle size of less than 0.5 mm, and then sieving it under a 50-mesh sieve to obtain alloy coarse powder; placing the crushed alloy coarse powder and zirconia balls in a zirconia tank at a mass ratio of 18:1, and ball milling for 24 hours under the protection of anhydrous ethanol, with a ball mill speed of 350 r / min;

[0028] (4) The ball-milled powder was taken out of a nitrogen-protected glove box, dried, and pressed into a billet with a diameter of 20 mm and a height of 10 mm;

[0029] (5) placing the blank into a vacuum microwave sintering furnace for high-temperature sintering at a temperature of 1040° C. for 30 min at a microwave frequency of 3.2 kW to obtain a sintered blank;

[0030] (6) The obtained sintered blank was crushed, ground into fine powder using an agate mortar, and then sieved through a 200-mesh sieve to obtain alloy absorbing powder.

[0031] Embodiment 2:

[0032] A YFe4B4 alloy magnetic absorbing material:

[0033] (1) Using metal Y, Fe, Mn, Sn, Si, and B with a purity of ≥99.9% as raw materials, according to YFe 3.1 Mn 0.8 Sn 0.1 B 3.5 Si 0.5 Atomic proportioning for batching;

[0034] (2) melting in a standard vacuum melting furnace under argon protection and casting to obtain an alloy ingot;

[0035] (3) crushing the obtained alloy ingot into coarse powder with a particle size of less than 0.5 mm, and then sieving it under a 50-mesh sieve to obtain alloy coarse powder; placing the crushed alloy coarse powder and zirconia balls in a zirconia tank at a mass ratio of 18:1, and ball milling for 16 hours under the protection of anhydrous ethanol, with a ball mill speed of 250 r / min;

[0036] (4) The ball-milled powder was taken out of a nitrogen-protected glove box, dried, and pressed into a billet with a diameter of 20 mm and a height of 10 mm;

[0037] (5) placing the blank into a vacuum microwave sintering furnace for high-temperature sintering at a temperature of 1000° C. for 40 min at a microwave frequency of 2.7 kW to obtain a sintered blank;

[0038] (6) The sintered blank was crushed and ground into fine powder using an agate mortar, and then sieved through a 200-mesh sieve to obtain alloy absorbing powder.

[0039] Embodiment 3:

[0040] A YFe4B4 alloy magnetic absorbing material:

[0041] (1) Using metal Y, Fe, Mn, Sn, Si, and B with a purity of ≥99.9% as raw materials, according to YFe 3.2 Mn 0.2 Sn 0.6 B 3.1 Si 0.9 Atomic proportioning for batching;

[0042] (2) melting in a standard vacuum melting furnace under argon protection and casting to obtain an alloy ingot;

[0043] (3) crushing the obtained alloy ingot into coarse powder with a particle size of less than 0.5 mm, and then sieving it under a 50-mesh sieve to obtain alloy coarse powder; placing the crushed alloy coarse powder and zirconia balls in a zirconia tank at a mass ratio of 18:1, and ball milling for 10 hours under the protection of anhydrous ethanol, with the ball mill speed of 300 r / min;

[0044] (4) The ball-milled powder was taken out of a nitrogen-protected glove box, dried, and pressed into a billet with a diameter of 20 mm and a height of 10 mm;

[0045] (5) placing the blank into a vacuum microwave sintering furnace for high-temperature sintering at a temperature of 1060° C. for 20 min at a microwave frequency of 2.0 kW to obtain a sintered blank;

[0046] (6) The obtained sintered blank was crushed, ground into fine powder using an agate mortar, and then sieved through a 200-mesh sieve to obtain alloy absorbing powder.

[0047] Detection:

[0048] The alloy absorbing powders obtained in the above embodiments 1-3 were mixed with paraffin in a mass ratio of 17:3 to prepare coaxial samples with inner and outer diameters of 3 mm and 7 mm, respectively, and thicknesses of 1.0 mm, 1.3 mm, 1.6 mm, 1.9 mm, 2.2 mm, and 2.5 mm, respectively. The complex magnetic permeability and complex dielectric constant of the coaxial samples in the 2-8 GHz frequency band were measured using an HP8722ES microwave vector network analyzer.

[0049] The reflectivity R of the single-layer absorbing material is calculated according to formula (1) using the measured complex magnetic permeability and complex dielectric constant data;

[0050]

[0051] Where ε r , μ r and d are the relative dielectric constant, relative magnetic permeability and thickness of the absorbing material, respectively, f is the frequency of the electromagnetic wave, C is the propagation speed of the electromagnetic wave in free space (i.e., the speed of light), and j is an imaginary unit.

[0052] Wherein YFe in Example 1 3.2 Mn 0.5 Sn 0.3 B 3.8 Si 0.2 Alloy absorbing powder test results are shown in Figure 2 ,from Figure 2It can be seen that in all thicknesses, the minimum reflectivity peak is less than -10dB (absorption rate is greater than 90%), and has a good broadband effect. When the composite thickness is 1.0mm, the minimum reflectivity peak reaches about -31.9dB at 4.8GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -28.3dB at 4.1GHz; when the thickness is 1.6mm, the minimum reflectivity peak reaches about -29.8dB at 3.6GHz; when the composite thickness is 1.6mm, the minimum reflectivity peak reaches about -29.8dB at 3.6GHz; when the composite thickness is 1.0mm, the minimum reflectivity peak reaches about -31.9dB at 4.8GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -28.3dB at 4.1 ...3mm, the minimum reflectivity peak reaches about -28.3dB at 4.1GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -31.9dB at 4.8GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -31.9dB at 4.8GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -31.9dB at 4.8GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -31.9dB at 4.8GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -31. When the thickness of the composite is 1.9mm, its minimum reflectivity peak value is about -30.2dB at 3.2GHz; when the thickness of the composite is 2.2mm, its minimum reflectivity peak value is about -30.0dB at 2.8GHz; when the thickness of the composite is 2.5mm, its minimum reflectivity peak value is about -26.4dB at 2.6GHz; when the thickness of the composite is between 1.6-2.5mm, the minimum reflectivity of this composite falls between the S band (2-4GHz), and it has excellent microwave absorption effect and bandwidth.

[0053] In Example 2, YF e3.1 Mn 0.8 Sn 0.1 B 3.5 Si 0.5 Alloy absorbing powder test results are shown in Figure 3 ,from Figure 3 It can be seen that in all thicknesses, the minimum reflectivity peak is less than -10dB (absorption rate is greater than 90%), and has a good broadband effect. When the composite thickness is 1.0mm, the minimum reflectivity peak reaches about -28.4dB at 5.6GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -39.3dB at 4.5GHz; when the thickness is 1.6mm, the minimum reflectivity peak reaches about -36.3dB at 3.84GHz; when the composite thickness is 1.6mm, the minimum reflectivity peak reaches about -36.3dB at 3.84GHz; when the composite thickness is 1.0mm, the minimum reflectivity peak reaches about -28.4dB at 5.6GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -39.3dB at 4.5 ...3mm, the minimum reflectivity peak reaches about -39.3dB at 4.5GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -39.3dB at 4.5GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -39.3dB at 4.5GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -39.3dB at 4.5GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -39.3dB at 4.5GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about - When the thickness of the composite is 1.9mm, its minimum reflectivity peak reaches about -36.5dB at 3.3GHz; when the thickness of the composite is 2.2mm, its minimum reflectivity peak reaches about -46.9dB at 2.8GHz; when the thickness of the composite is 2.5mm, its minimum reflectivity peak reaches about -29.6dB at 2.4GHz; when the thickness of the composite is between 1.6-2.5mm, the minimum reflectivity of this composite falls between the S band (2-4GHz), and it has excellent microwave absorption effect and bandwidth.

[0054] Example 3 YFe 3.2 Mn 0.2 Sn 0.6 B 3.1 Si 0.9 Alloy absorbing powder test results are shown in Figure 4 ,from Figure 4 It can be seen that in all thicknesses, the minimum reflectivity peak is less than -10dB (absorption rate is greater than 90%), and has a good broadband effect. When the composite thickness is 1.0mm, the minimum reflectivity peak reaches about -28.9dB at 5.4GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -28.7dB at 4.6GHz; when the thickness is 1.6mm, the minimum reflectivity peak reaches about -27.9dB at 3.80GHz; when the composite thickness is 1.3mm, the minimum reflectivity peak reaches about -28.7dB at 4.6GHz; when the composite ... When the thickness of the composite is 1.9mm, its minimum reflectivity peak reaches about -28.1dB at 3.2GHz; when the thickness of the composite is 2.2mm, its minimum reflectivity peak reaches about -30.4dB at 2.8GHz; when the thickness of the composite is 2.5mm, its minimum reflectivity peak reaches about -29.3dB at 2.5GHz; when the thickness of the composite is between 1.6-2.5mm, the minimum reflectivity of this composite falls between the S band (2-4GHz), and it has excellent microwave absorption effect and bandwidth.

[0055] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0056] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A YFe4B4 alloy magnetic absorbing material, characterized in that: The alloy magnetic wave absorbing material has the following atomic ratio: YFe 4-x-y Mn x Sn y B 4-z Si z ; The preparation method of the alloy magnetic wave absorbing material comprises the following steps: (1) Ingredients: Select metal Y, Fe, Mn, Sn, Si, and B as raw materials, according to YFe 4-x-y Mn x Sn y B 4-z Si z The raw material mixture is prepared by the atomic ratio, and the atomic ratio is 0.1≤x≤0.8; 0.2≤y≤0.6; 0.1≤z≤0.8; (2) Melting: Melting the mixture in a vacuum melting furnace and casting to obtain an alloy ingot; (3) Ball milling: crushing the alloy ingot to prepare alloy coarse powder, and then ball milling the alloy coarse powder to obtain ball milled powder for later use; (4) Molding: The ball-milled powder is taken out of a nitrogen-protected glove box, dried, and then pressed into a blank; (5) Sintering: sintering the above blank at high temperature to obtain a sintered blank for later use; (6) Grinding: The sintered blank is taken out and crushed, then ground and sieved to obtain alloy absorbing powder.

2. The YFe4B4 alloy magnetic wave absorbing material according to claim 1, characterized in that: The smelting in step (2) needs to be carried out under argon protection.

3. The YFe4B4 alloy magnetic wave absorbing material according to claim 1, characterized in that: In the step (3), the alloy coarse powder is sieved through a 50-mesh sieve, and during ball milling, the alloy coarse powder and zirconium oxide balls are placed in a zirconium oxide tank at a mass ratio of 18:1, and ball milled for 24 hours under the protection of anhydrous ethanol, wherein the ball mill speed is 350 r / min.

4. The YFe4B4 alloy magnetic wave absorbing material according to claim 1, characterized in that: In step (4), the diameter of the blank is 20 mm and the height is 10 mm.

5. The YFe4B4 alloy magnetic wave absorbing material according to claim 1, characterized in that: In the step (5), a vacuum microwave sintering furnace is used to sinter the blank, wherein the sintering temperature is 1000-1060° C., the sintering time is 20-40 min, and the microwave frequency is 2.0-3.2 kW.

6. The YFe4B4 alloy magnetic wave absorbing material according to claim 1, characterized in that: In the step (6), the alloy absorbing powder needs to pass through a 200-mesh sieve.

Citation Information

Patent Citations

  • Rare earth permanent magnet alloy material and preparation process thereof

    CN102610347A

  • Rare earth sintered magnet and its making method

    CN103377791A